2001
DOI: 10.1021/bi010330b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen-Bond Networks in Controlling Reduction Potentials in Desulfovibrio vulgaris (Hildenborough) Cytochrome c3 Probed by Site-Specific Mutagenesis

Abstract: Cytochromes c 3 isolated from DesulfoVibrio spp. are periplasmic proteins that play a central role in energy transduction by coupling the transfer of electrons and protons from hydrogenase. Comparison between the oxidized and reduced structures of cytochrome c 3 isolated from DesulfoVibrio Vulgaris (Hildenborough) show that the residue threonine 24, located in the vicinity of heme III, reorients between these two states [Messias, A. C., Kastrau, D. H. W., Costa, H. S., LeGall, J., Turner, D. L., Santos, H., an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Since there is no apparent correlation between the interaction energy and the relative orientation of the haems, the charge was considered to be localised on the iron. Interactions involving acid–base centres were only considered for the cases of Dgc3, DvHc3 and DvMc3 in which the primary acid–base centre is unambiguously identified as the propionate 13 of haem I [20,24,25] and in this case the average position of the carboxylate oxygen atoms was considered as the location of the charge.…”
Section: Resultsmentioning
confidence: 99%
“…Since there is no apparent correlation between the interaction energy and the relative orientation of the haems, the charge was considered to be localised on the iron. Interactions involving acid–base centres were only considered for the cases of Dgc3, DvHc3 and DvMc3 in which the primary acid–base centre is unambiguously identified as the propionate 13 of haem I [20,24,25] and in this case the average position of the carboxylate oxygen atoms was considered as the location of the charge.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction potentials of the hemes in cyts c 3 are also dependent on the pH, called the redox-Bohr effect, 340342 due to the interactions of the heme propionates in the H-bonding network and/or electrostatic interactions with the residues in the vicinity. 341,343345 …”
Section: Cytochromes In Electron Transfer Processesmentioning
confidence: 99%
“…Because molybdate was found to function as an electron acceptor from dithionite-reduced G20c 3 , and preliminary data from a site-directed mutant K14A of G20c 3 showed that molybdate could no longer oxidize this mutant protein (S. Miller & J.D.W., unpublished results), we infer that heme IV may be the primary site of electron exit from the protein, in agreement with other results. 12,20,41,44 Moreover, we predict that Lys56 is essential for reduction of molybdate, and possibly uranyl acetate, by G20c 3 . This prediction will be tested by mutagenesis studies.…”
Section: Molybdate-bound G20c 3 Structurementioning
confidence: 82%